TOWARD ENHANCED STOCK VALUE: Exploring the Nexus of Financial Performance, Company Size, and Dividend Policy in Optimization Strategies - Pratiwi, Endang (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2023)
In Indonesia, the development of basic industrial and chemical companies is quite rapid, it can be seen from the development of basic industrial and chemical companies listed on the Indonesia Stock Exchange (IDX) or becoming public companies from year to year increasing. The purpose of this study is to determine and analyze dividend policy, moderate the size of the company against the share price of manufacturing companies in the basic industrial and chemical sectors listed on the Indonesia Stock Exchange. The method used is the titative descriptive method. The total research population is 88 companies while the number of research samples is 20 companies. Before testing the hypothesis, the researcher first uses the classical assumption test consisting of the normality test, hetoregenity test, autocorrelation test, and multicollinearity test. The results of the study with Moderated Regression Analysis (MRA) testing show that the Dividend Policy is able to moderate the influence of Company Size on Share Prices in Basic Industrial and Chemical Companies listed on the Indonesia Stock Exchange